Defining the illness trajectory of metastatic breast cancer. Issue 4 (23rd July 2013) - Reed, Elizabeth; Corner, Jessica
Abstract : Background: With significant developments in the management of metastatic breast cancer, the trajectory of progressive breast cancer is becoming increasingly complex with little understanding of the illness course experienced by women, or their ongoing problems and needs. Aim: This study set out to systematically explore the illness trajectory of metastatic breast cancer using models from chronic illness as a framework. Design: Longitudinal mixed methods studies detailing each woman's illness trajectory were developed by triangulating of narrative interviews, medical and nursing documentation and an assessment of functional ability using the Karnofsky Scale. The Corbin and Strauss Chronic Illness Trajectory Framework was used as a theoretical framework for the study. Participants: Ten women aged between 40 and 78 years, with metastatic breast cancer. Results: Women's illness trajectories from diagnosis of metastatic disease ranged from 13 months to 5 years and 9 months. Eight of the 10 women died during the study. Chronic illness trajectory phases identified by Corbin and Strauss (pretrajectory, trajectory onset, living with progressive disease, downward phase and dying phase) were experienced by women with metastatic breast cancer. Three typical trajectories of different duration and intensity were identified. Women's lives were dominated by the physical burden of disease and treatment with little evidence of symptom control or support. Conclusions: This is the first study to systematically explore the experience of women over time to define the metastatic breast cancer illness trajectory and provides evidence that current care provision is inadequate. Alternative models of care which address women's increasingly complex problems are needed.